On estimating quality of elderly monitoring service based on sensor reliability. Issue 1 (2nd January 2017) - Tokunaga, Seiki; Saiki, Sachio; Matsumoto, Shinsuke; Nakamura, Masahide
Abstract: Remote monitoring service for elderly people is an effective method to support elderly people with safe. In this paper, we tackle to reveal the relationships between quality of elderly monitoring service and sensor reliability in remote monitoring service. To achieve the above goal, we propose four step methods, generalization by three-actor model, designing the algorithms of the three-actor and simulation of RMS. Moreover, we construct the elderly model based on the statistics report. Our most important contribution shows that the guideline, which shows the references between sensor accuracy and reliability of RMS. This guideline will provide benefit for RMS service provider and end-user.